Analysis of GLT6D1 and CDKN2BAS gene polymorphisms in Brazilian patients with advanced periodontitis - Rodrigues, Richelle Soares; Rêgo, Rodrigo; Caminaga, Raquel Mantuaneli Scarel [UNESP]; Goveia, Jéssica Marina [UNESP]; Silveira, Virginia Régia Souza (FapUNIFESP (SciELO), 2022)
Gene polymorphisms can predispose to periodontal disease, as demonstrated by the well-documented association between aggressive periodontitis and single nucleotide polymorphisms (SNPs) such as rs153745 in the GLT6D1 gene and rs3217992 in the CDKN2BAS gene. The purpose of this study was to evaluate the presence of these SNPs in Brazilian patients with advanced periodontitis (stages III/IV, Grade B/C) vs. healthy controls. A total of 100 patients with periodontitis (Group BC) were enrolled. Of these, 51 patients were classified as stage III and 49 patients were classified as stage IV, and 52 were Grade B (Group B) and 48 were Grade C (Group C). The control Group consisted of 61 healthy subjects. DNA samples extracted from buccal epithelial cells were used to genotype the SNPs rs1537415 (GLT6D1) and rs3217992 (CDKN2BAS) by real-time quantitative PCR. No significant differences in polymorphism frequency were found between the control Group and each of the patient groups (BC, B, or C), and Group B did not differ from Group C. In conclusion, the evaluated SNPs had no significant influence on the prevalence of periodontal disease in the sampled Brazilian population.
Keywords: Genetic; Periodontitis; Polymorphism; Single nucleotide